Aplicación del taller de canto en la creatividad en niños de la Institución Educativa Inicial N°430 San José de Verseba, Ramón Castilla 2023 - Sangama Garcia, Rosana (2024)
The purpose of this study was to determine the effect of the application of the singing workshop on the creativity of children from the Institution Educative Initial N°430 San José de Verseba, Ramón Castilla, in 2023. Using an applied quantitative research approach, it was designed an experiment with two groups: one control and one experimental, with a total population of 51 children. Data collection was carried out through observation, using an observation guide validated by experts. The results showed that, before the intervention, both groups had similar standard deviations in creativity. However, after the singing workshop, a significant increase in the creativity of the experimental group was observed, with a standard deviation of 31.04 ± 3.072, compared to the control group, which obtained 27.44 ± 2.656. This increase is directly attributed to the singing workshop. In conclusion, the application of the singing workshop has a significant effect on the development of children's creativity at the Institution Educative Initial N°430 San José de Verseba, Ramón Castilla, in 2023.